2018
DOI: 10.1177/0886260518776999
|View full text |Cite
|
Sign up to set email alerts
|

Is There Really a Relationship Between Empathy and Aggression? Evidence From Physiological and Self-Report Measures

Abstract: A strong relationship between empathy and aggression has traditionally been argued, but a recent meta-analysis showed that this relationship is surprisingly weak. However, none of the studies that were analyzed in the meta-analysis used physiological measures of empathy to assess differences between aggressive and nonaggressive subjects. The present study evaluated the activity of the corrugator and zygomatic muscles, galvanic skin response, and heart rate response to pictures with different social content in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 43 publications
4
47
0
4
Order By: Relevance
“…Recent studies show that positive empathy lead to the emergence of prosocial behavior (Morelli, Lieberman, & Zaki, 2015;Telle & Pfister, 2015), feeling of social connection, and subjective well-being (Morelli et al, 2015). Additionally, a research conducted by Gantiva and Cendales (2018) showed that aggressiveness is negatively associated with cognitive empathy, but not with affective empathy. The results of these studies show the importance of empathy in a child's life.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that positive empathy lead to the emergence of prosocial behavior (Morelli, Lieberman, & Zaki, 2015;Telle & Pfister, 2015), feeling of social connection, and subjective well-being (Morelli et al, 2015). Additionally, a research conducted by Gantiva and Cendales (2018) showed that aggressiveness is negatively associated with cognitive empathy, but not with affective empathy. The results of these studies show the importance of empathy in a child's life.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the second line of convergent validity that evaluated the relationship between the adapted EQ scales and aggression, it was established that high CE was related to low levels of physical aggression (as it was described recently by Gantiva et al, 2018), and that more ER scores are related to lower levels of physical aggression, anger and hostility. By this same token, SS were high in individuals that reported low levels of physical aggression, anger and hostility.…”
Section: Discussionmentioning
confidence: 89%
“…These results support the observed by Bennet et al (2005), who propose that women would have superior prosocial skills and reduced aggression in comparison to men, being attributable to sex differences in socio cognitive skills. A meta-analysis by Gantiva et al (2018), established that less cognitive empathy is characteristic of aggressive individuals, but this is not the case for affective empathy. Nonetheless, a recent work found that affective empathy is associated with aggression and sex differences, but not cognitive empathy (Dryburgh & Vachon, 2019).…”
mentioning
confidence: 99%
“…Otros estudios (Richaud, Lemos y Oros, 2013) destacan el valor de la regulación de las emociones para el desarrollo de la conducta moral, como así también en el bienestar personal en la infancia (Eisengberg, Fabes y Spinrad, 2006) y la adolescencia (Zorza y Becaría, 2014). Además, hay otras evidencias sobre la baja modulación de la respuesta emocional como predictor de la conducta agresiva (Gantiva et al, 2018;Garaigordobil, Martínez y Aliri, 2013;Zorza, Marino, de Lemus y Acosta Mesas, 2013).…”
Section: Discussionunclassified
“…Este hallazgo fue consistente en los tipos específi cos de agresión: verbal, física y sexual (Vachon, Lynam y Johnson, 2013). Otro estudio reciente (Gantiva, Cendales, Díaz y González, 2018) utilizó medidas de reacciones fi siológicas (conductancia de la piel, ritmo cardíaco y actividad cigomática del rostro) ante imágenes de interacción positivas y negativas, junto con medidas autoinformadas de empatía en adultos jóvenes. Los resultados no indicaron diferencias signifi cativas en las medidas fi siológicas de respuesta a estímulos afectivos sociales en los sujetos agresivos y no agresivos; sólo encontraron diferencias signifi cativas en la subescala de la Toma de perspectiva, que mide la empatía cognitiva.…”
unclassified